A validation study of the Malay version of career commitment questionnaire - N. Rasudin, Syahmina; Shohaimi, Shamarina (Medip Academy, 2017)
Background: An employee’s commitment to his career is an important aspect in ensuring organisational effectiveness. Low level of commitment may increase withdrawal rates, thus, will negatively affect the organisation. The career commitment level of an employee needs to be measured properly. Hence, a validated and reliable instrument is very important to measure the level of career commitment among employees. Career Commitment Questionnaire (CCQ) consists of a combination of Blau’s Measure and Career Commitment Measure (CCM). Methods: The CCQs were distributed to secondary school teachers from 30 schools in Kota Bharu district. The collected questionnaires were split into Exploratory Factor Analysis (EFA) and Confirmatory Factor Analysis (CFA). Respondents answered the instrument by self-administered. Data were analysed for EFA, CFA, internal consistency, and convergent validity using STATA software Version 14. Results: The EFA resulted in the production of 1 factor with 19 items, while CFA results confirmed the construction of 1 factor with 19 items showed by the value of Chi square/df (1.631), TLI (0.967), CFI (0.971), and RMSEA (0.078)which met the requirements of model fitness. The overall Cronbach’s alpha value of CCQ was 0.99. The Average Variance Extracted (AVE) of CCQ was 0.78 indicating that the convergent validity was met. Conclusions: To recapitulate, the CCQ was proved to be a validated and reliable instrument for measuring the level of career commitment among school teachers and in future should be tested to ensure the suitability of CCQ in different career fields.